Pengaruh Variabel Sosio-Demografis terhadap Mobilitas Ulang-Alik di Jabodetabek - Warsida, Rotua Y.; Adioetomo, Sri M.; Pardede, Elda L. (UI Scholars Hub, 2013)
This study aims to explain the effect of socio-demographic variables i.e. sex, wage, employment status, and marital status on commuting in Jabodetabek. The result of binary logistic regression using Sakernas 2012 shows that male are more likely to commute than female. Male in formal sector have the highest probability to commute while by marital status, unmarried male have the highest probability to commute. The level of wage is positively related with the probability to commute although at certain level of wage, an increase in wage increases probability to commute among male lower than probability to commute among female.